Suicidal Risk, Psychopathology, and Quality of Life in a Clinical Population of Adolescents - Balazs, Judit; Miklosi, Monika; Halasz, Jozsef; Horváth, Lili Olga; Szentiványi, Dóra; Vida, Péter (Frontiers in Psychiatry, 2018)
Background. According to literature data, psychopathology is associated with both quality of life (QoL) and suicidal risk in adolescents, but the literature does not fully support a direct association between psychopathology and suicidal thoughts and behaviors. The aim of the present study was to investigate the possible mediational role of QoL in the relationship between psychopathology and level of suicidal risk in a clinical sample of adolescents. Method. The authors examined a clinical population of 134 adolescents, aged 13-18 years. Suicidal risk – having any current suicidal ideations and/or previous suicide attempt – was assessed by the Mini International Neuropsychiatric Interview. QoL was evaluated by the adolescent self-rated versions of “Das Intervertar zur Erfassung der Lebensqualität Kindern und Jugendlichen” (ILK: Measure of Quality of Life for Children and Adolescents) and psychopathology was measured by adolescent self-rated versions of the Strengths and Difficulties Questionnaire (SDQ). A mediational model, in which QoL mediated the relationship between psychopathology and suicidal risk controlling for gender and age, was tested by means of regression analyses. Results. Gender and age were both associated with suicidal risk. Self-reported QoL significantly mediated the relationships between emotional problems (=1.846; 95% BCa CI: .731 — 2.577), as well as peer problems (=.883; 95% BCa CI: .055 — 1.561) and suicidal risk: more emotional and peer problems were associated with lower QoL, which in turn was related to higher level of suicidal risk. Conclusions. Based on the current study, which aims to make further steps in suicidal prevention, our findings suggest that clinicians should routinely screen the QoL of their patients, especially in adolescents with emotional and peer problems. Furthermore it is important to focus intervention and treatment efforts on improving the OoL of adolescents with with emotional and peer problems.